A Magyar Királyi 2. Honvéd Hadsereg harcai 1942-43-ban : Vázlatos áttekintés - Pintér, István (Közép-Európai Közlemények, 2013)
In this study I write about the getting to the front, the first fights, the defence of the River Don, the break-through, the losses and the assessment of the fights of the Second Hungarian Royal Army in 1942–43. I mention among the controversial facts, that we got operational technology from the Germans, the Hungarian and the Hungarian-German troops did their best for the occupation of the three bridgeheads, which were on the River Don. I write that Knight nagybányai István Horthy deputy-governor, reservist and Mister flying officer killed in action on 20 August, 1942. I feel that Hungarian military leadership (Gusztáv Jány, Ferenc Szombathelyi, Vilmos Nagy nagybaczoni) did their best in order to facilitate by the situation of the army. The so-colled Crammer corps weren’t allowed to put into action by the Germans, and it was the only reserve for the Germans ont he 600-700 kilometres front section. I refute the extremely lying charge, that this army would run away cowardly for the first gunshot and I prove it too. I mention that there were cruel fights for days and the commander of the attacking Red Army wrote that the break-through was on 13 January 1943. In this study you can read about the heroic defence of Osztrogorszk, Alekszejevka and Ilinka. The loss of the 2nd H. R. Army was about 125–128 000 persons, and the loss of the Red Army was about 100–155 000 persons. This fact in itself refutes the charge of the immediately running away. The publication of the loss of the Red Army hasn’t been allowed for 40–50 years. It is true that the Russian troops broke-through the front but the 2nd H. R. Army were correct to the best of their power. The Red Army couldn’t surround and destroy them.